2021
DOI: 10.1002/anie.202109349
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Cu+ Ions in Live Cells via Fluorescence Lifetime Imaging Microscopy

Abstract: Copper is an essential trace element in living organisms with its levels and localisation being carefully managed by the cellular machinery. However, if misregulated, deficiency or excess of copper ions can lead to several diseases. Therefore, it is important to have reliable methods to detect, monitor and visualise this metal in cells. Herein we report a new optical probe based on BODIPY, which shows a switchon in its fluorescence intensity upon binding to copper(I), but not in the presence of high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…[55] For Cu 2+ detection, the first step always represents chelation or complexation between copper ions and atoms with lone pairs such as nitrogen, oxygen atoms in sensor skeleton. [56,57] Then, transfer of photoinduced electron (PET), excited-state intramolecular proton (ESIPT), and Förster resonance energy (FRET) mechanisms result in a change of optical properties of sensors to achieve selective sensing of copper ions. Among the three possible mechanisms PET principle is most exiled which just involves enhancing excited electron transfer or hindering this process without requiring close proximity between proton donor and proton acceptor in the backbone of sensors or strict spectral overlap between emission spectra of donor and absorption spectra of acceptor.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…[55] For Cu 2+ detection, the first step always represents chelation or complexation between copper ions and atoms with lone pairs such as nitrogen, oxygen atoms in sensor skeleton. [56,57] Then, transfer of photoinduced electron (PET), excited-state intramolecular proton (ESIPT), and Förster resonance energy (FRET) mechanisms result in a change of optical properties of sensors to achieve selective sensing of copper ions. Among the three possible mechanisms PET principle is most exiled which just involves enhancing excited electron transfer or hindering this process without requiring close proximity between proton donor and proton acceptor in the backbone of sensors or strict spectral overlap between emission spectra of donor and absorption spectra of acceptor.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…[8] Ca 2+ sensing is reviewed extensively in the literature and not discussed further here; rather it serves as a high-water mark for what biosensors can achieve. Indeed, the remarkable successes in sensing Ca 2+ inspired the creation of sensors of chloride, [9] Cu + [10] as well as important metabolites such as cAMP [11] and nicotinamide adenine dinucleotides. [12] Other analyte sensors are sure to follow.…”
Section: Sensing Of Ions and Metabolitesmentioning
confidence: 99%
“…7–9 This kind of chemodynamic therapy has been widely used in antitumor research. 10–12 In addition, the previous studies have demonstrated that copper can promote the growth of endothelial cells and angiogenesis. 13–15 Therefore, reducing the content of copper in cells via copper chelators can inhibit the growth of cells and angiogenesis.…”
Section: Introductionmentioning
confidence: 98%